PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR FISIKA SISWA - Millah, Mailulatul; Wildani, Arin (EduFisika: Jurnal Pendidikan Fisika, 2023)
This research was conducted to know the effect of applying the CTL learning model assisted by snakes and ladders media on student learning outcomes. This research is experimental research with a pretest-posttest control group design. The population in this study were all MIPA Putri MA students in Pamekasan, while the sample consisted of two groups, namely the experimental class and the control class, with a purposive sampling technique. The experimental class and control class samples each consisted of 30 students. The experimental class was given the CTL model learning treatment with the help of ladder snakes, while the control class was given the Discovery Learning (DL) model. The instrument used in this study was an instrument to test students' physics learning outcomes in the C1-C4 cognitive domain in the form of multiple-choice questions. Data collection is done through tests. Data analysis used the Ancova test with the pretest results as the control variable. The results showed that the significance value obtained was <0.001 (<0.05), meaning that the CTL model assisted by snakes and ladders media significantly affects student learning outcomes.